1969
DOI: 10.2307/144675
|View full text |Cite
|
Sign up to set email alerts
|

Labor-Supply Effects of Income, Income-Work, and Wage Subsidies

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of Wisconsin Press andThe Board of Regents of the University of Wisconsin System are collaborating with JSTOR to digitize, preserve and extend access to The Journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This should not be surprising since benefits are no longer paid to nonworkers under a wage or earnings subsidy, and, from a equity and distributional point of view, a progressive tax system is replaced by a regressive one. As this early literature recognized (Kesselman, 1969;Barth and Greenberg, 1971), and has been noted in this review, replacing an income support program with such a subsidy would require a categorization of the eligible population which has its own difficulties.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…This should not be surprising since benefits are no longer paid to nonworkers under a wage or earnings subsidy, and, from a equity and distributional point of view, a progressive tax system is replaced by a regressive one. As this early literature recognized (Kesselman, 1969;Barth and Greenberg, 1971), and has been noted in this review, replacing an income support program with such a subsidy would require a categorization of the eligible population which has its own difficulties.…”
mentioning
confidence: 93%
“…Graphically, this is identical to Figure 9 except that those initially off welfare, on segment DE, are also eligible. The relative merits of wage-rate and earnings subsidies, on the one hand, and a negative income or similar income support program with a G and t, on the other, were debated extensively in the late 1960s and early 1970s (e.g., Barth and Greenberg, 1971;Garfinkel, 1973;Kesselman, 1969Kesselman, , 1973Zeckhauser, 1971). That literature showed that there will almost certainly be positive effects on labor supply if an income support program is completely replaced by a wage or earnings subsidy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the economic literature on income maintenance (Green, 1968;Kesselman, 1969), the analysis of work discentives and other effects from income manipulation proceeds as if, aside from universalistic considerations such as gender and physical condition of the family head, the poverty population can be treated as a homogeneous group. In this paper we have attempted to demonstrate the deficiency of that simplification.…”
Section: Discussionmentioning
confidence: 99%
“…By bringing individuals out of unemployment or other benefit receipt schemes, wage subsidies are in theory a powerful tool for reducing the welfare loss of unemployment (Kaldor 1936, Kessleman 1969, Phelps 1994, Calmfors 1994, i.e., the utility loss from being out of work. By lowering unemployment, subsidies can lessen employer contributions to social insurance.…”
Section: Introductionmentioning
confidence: 99%